Surface morphology and deuterium retention in W and W-HfC alloy exposed to high flux D plasma irradiation - Yongkui Wang; Xiaochen Huang; Jiafeng Zhou; Jun Fang; Yan Gao; Jinlong Ge; Shu Miao; Zhuoming Xie (Nuclear Engineering and Technology, 2023)
In this work, pure W and W-0.5wt%HfC alloy (WHC05) were fabricated by sintering and hot-rolling following the same processing route. After exposing to a high flux deuterium plasma irradiation with the D+ flux to three fluences of 6.00 × 1024, 2.70 × 1025 and 7.02 × 1025 D/m2, the evolution of surface morphology, deuterium retention and hardening behaviors in pure W and WHC05 has been studied. The SEM results show the formation of D blisters on the irradiated area, and with the increase of D implantation, the size of these blisters increases from 200 ∼ 500 nm (2.70 × 1025 D/m2) to 1 ∼ 2 μm (7.02 × 1025 D/m2) in WHC05 and from 1 ∼ 2 μm (2.70 × 1025 D/m2) to > 3 μm (7.02 × 1025 D/m2) in pure W, respectively. A higher D retention and obvious hardening are observed in pure W than that of the WHC05 alloy, indicating an improve radiation resistance in WHC05 compared to pure W.